Rising NPAs: A Nightmare for Banking Industry - Duhoon, Anshu (International Journal of Psychosocial Rehabilitation, 2024)
Banks’s performance is the true reflection of economy of any country. The Indianbanking system has been facing serious problem of non- performing assets. NPA’s reflects thestatus of liquidity, Banks’s management efficiency, net worth, profitability and eroded value ofassets of any banking company. The sound financial position of any company is reflected by levelof NPA’s in that particular industry. Growth in NPA reflects that there is a need of strengthenthe credit appraisal system of that industry because it shows the poor credit management systemof the banks and it has negative effect on profitability of banks. The Indian banking system isfacing the problem of continuously increment in level of NPA. This paper analyses the status ofrecovery mechanism through i.e. PROJECT SAKSHAT, SARFAESI Act, One time settlement(OTS) scheme, Lok-adalats and debt –recovery tribunals. This research paper also deals withcapital adequacy norms regarding NPAs, major reason for conversion of loans into NPAs and tosuggest measure for efficient management of NPA’s for improving both profitability and liquidityposition of banking industry